Huashi baidu granule in the treatment of pediatric patients with mild coronavirus disease 2019: A single-center, open-label, parallel-group randomized controlled clinical trial - Chen, Jiande; Tang, Qiuyu; Zhang, Baoqin; Yuan, Shuhua; Chen, Jia; Shen, Shiyu; Wang, Dong; Lin, Jilei; Dong, Hongliang; Yin, Yong; Gao, Jian (Frontiers in Pharmacology, 2023)
Background: Since late February 2022, a wave of coronavirus disease 2019 (COVID-19) mainly caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Omicron variant rapidly appeared in Shanghai, China. Traditional Chinese medicine treatment is recommended for pediatric patients; however, the safety and efficacy remain to be confirmed. We conducted a single-center, open-label, parallel-group randomized controlled trial to assess the efficacy and safety of a Chinese herb compound, Huashi Baidu granule (HSBDG) in pediatric patients with laboratory-confirmed mild COVID-19. Methods: 108 recruited children (aged 3 to 18 years) with laboratory-confirmed mild COVID-19 were randomly allocated 2:1 to receive oral HSBDG for 5 consecutive days (intervention group) and to receive compound pholcodine oral solution for 5 consecutive days (control group). The negative conversion time of SARS-CoV-2 nucleic acid and symptom scores were recorded. Results: The median negative conversion time of SARS-CoV-2 nucleic acid was significantly shorter in the intervention group than in the control group (median days [interquartile range (IQR)]: 3 [3-5] vs. 5 [3-6]; P = 0.047). The median total symptom score on day 3 was significantly lower in the intervention group than in the control group (median total symptom score [IQR]: 1 [0-2] vs. 2 [0-3]; P = 0.036). There was no significant differences in the frequency of antibiotic use and side effects between the two groups. Conclusions: HSBDG is a safe, effective oral Chinese herbal compound granule, which shows a good performance within the Omicron wave among pediatric patients. Trial registration: ClinicalTrials.gov, number NCT05501288.